Report of the European Society of Cardiology Cardiovascular Round Table regulatory workshop update of the evaluation of new agents for the treatment of acute coronary syndrome: Executive summary. Issue 8 (December 2019) - Bueno, Héctor; de Graeff, Pieter; Richard-Lordereau, Isabelle; Emmerich, Joseph; Fox, Keith AA; Friedman, Carola P; Gaudin, Christophe; El-Gazayerly, Amany; Goldman, Samantha; Hemmrich, Melanie; Henderson, Robert A; Himmelmann, Anders; et al.
Regulatory authorities interpret the results of randomized controlled trials according to published principles. The European Medicines Agency (EMA) is planning a revision of the 2000 and 2003 guidance documents on clinical investigation of new medicinal products for the treatment of acute coronary syndrome (ACS) to achieve consistency with current knowledge in the field. This manuscript summarizes the key output from a collaborative workshop, organized by the Cardiovascular Round Table and the European Affairs Committee of the European Society of Cardiology, involving clinicians, academic researchers, trialists, European and US regulators, and pharmaceutical industry researchers. Specific questions in four key areas were selected as priorities for changes in regulatory guidance: patient selection, endpoints, methodologic issues and issues related to the research for novel agents. Patients with ST-segment elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) should be studied separately for therapies aimed at the specific pathophysiology of either condition, particularly for treatment of the acute phase, but can be studied together for other treatments, especially long-term therapy. Unstable angina patients should be excluded from acute phase ACS trials. In general, cardiovascular death and reinfarction are recommended for primary efficacy endpoints; other endpoints may be considered if specifically relevant for the therapy under study. New agents or interventions should be tested against a background of evidence-based therapy with expanded follow-up for safety assessment. In conclusion, new guidance documents for randomized controlled trials in ACS should consider changes regarding patient and endpoint selection and definitions, and trial designs. Specific requirements for the evaluation of novel pharmacological therapies need further clarification.